2020
DOI: 10.9734/csji/2020/v29i130152
|View full text |Cite
|
Sign up to set email alerts
|

Sythesis of Nano Zerovalent Iron Supported Sawdust (NZVI/SD) and Its Application for Removal of Arsenic (III) from Aqueous Solution

Abstract: Sawdust supported nano-zerovalent (NZVI/SD) iron was synthesized by treating sawdust with ferrous sulphate followed by reduction with NaBH 4 . The NZVI/SD was characterized by SEM, XRD, FTIR and Chemical method. Adsorption of As (III) by NZVI/SD was investigated and the maximum uptake of As (III) was found at pH value of 7.74 and equilibrium time of 3 hrs. The adsorption isotherm modelling revealed that the equilibrium adsorption data were better fitted with the Choudhury et al.; CSIJ, 29(1): 1-12, 2020; Artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Few research groups adopted treatment method using formaldehyde in sulfuric acid to enhance the adsorption capacity of sawdust but ended with poor results [29][30][31] . Recently we observed that sawdust impregnated with nano-zerovalent iron showed significant sorption of As(III) from aqueous solution 32 . Other recent studies showed that sawdust 33 , nano-sawdust 34 , sawdust-kaolinite composite 35 could be used as adsorbents for heavy metals.…”
Section: Introductionmentioning
confidence: 99%
“…Few research groups adopted treatment method using formaldehyde in sulfuric acid to enhance the adsorption capacity of sawdust but ended with poor results [29][30][31] . Recently we observed that sawdust impregnated with nano-zerovalent iron showed significant sorption of As(III) from aqueous solution 32 . Other recent studies showed that sawdust 33 , nano-sawdust 34 , sawdust-kaolinite composite 35 could be used as adsorbents for heavy metals.…”
Section: Introductionmentioning
confidence: 99%